2013
DOI: 10.1249/mss.0b013e31827205d1
|View full text |Cite
|
Sign up to set email alerts
|

Curvilinear Dose–Response Relationship of Carbohydrate (0–120 g·h−1) and Performance

Abstract: CHO beverage ingestion and endurance (∼160 min) performance appear to be related in a curvilinear dose-response manner, with the best performance occurring with a CHO (1:1:1 glucose-fructose-maltodextrin) ingestion rate of 78 g·h(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 33 publications
(81 reference statements)
6
57
0
1
Order By: Relevance
“…participants would be required to make meaningful comparisons between solutions, leaving no clear picture into the optimal dose of CHO. In a follow up investigation, Smith et al (2013) reported that optimal performance gains with CHO ingestion were likely to occur at rates as high as 78g·h -1 when consuming multiple forms of CHO. However, the optimal dose for the greatest improvement in performance was unclear in the 40 to 80g·h -1 range and interpretation is limited by the choice of study design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…participants would be required to make meaningful comparisons between solutions, leaving no clear picture into the optimal dose of CHO. In a follow up investigation, Smith et al (2013) reported that optimal performance gains with CHO ingestion were likely to occur at rates as high as 78g·h -1 when consuming multiple forms of CHO. However, the optimal dose for the greatest improvement in performance was unclear in the 40 to 80g·h -1 range and interpretation is limited by the choice of study design.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate (CHO) intake during exercise has consistently been shown to improve exercise performance (Smith et al, 2013;Smith et al, 2010) and extend exercise capacity (Galloway & Maughan, 2000;Watson, Shirreffs, & Maughan, 2012). CHO is thought to act in many ways to enhance performance: sparing of muscle glycogen (Bjorkman, Sahlin, Hagenfeldt, & Wahren, 1984;Stellingwerff et al, 2007); enhancing and maintaining elevated CHO oxidation rate; maintenance of blood glucose concentration (Coyle, Coggan, Hemmert, & Ivy, 1986); elevated exogenous CHO oxidation rate (Galloway, Wootton, Murphy, & Maughan, 2001); and central and peripheral neural up-regulation (Carter, Jeukendrup, & Jones, 2004;Chambers, Bridge, & Jones, 2009;Nikolopoulos, Arkinstall, & Hawley, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the consumption of large amounts of carbohydrate, Smith and colleagues recently demonstrated a curvilinear dose-response relationship of carbohydrate intake (fructose-glucose source ratio of 0.5, carbohydrate ingested in the range of 0-2.0 g/min) with endurance exercise performance with optimal performance identified at an ingestion rate of ~1.3 g/min (range 1.1-1.5 g/min) and decrements in performance observed at higher ingestion rates (Smith et al, 2013). Although not reported, it is possible that gastro-intestinal symptoms were influential in the reduction in performance at very high ingestion rates (i.e., >1.5 g/min).…”
Section: Sucrose Consumption During Exercise and Performancementioning
confidence: 99%
“…Despite carbohydrate intake rates of 78 g·h -1 (1:1:1 glucose-fructose-maltodextrin) during 2 h of steady state exercise being reported to be generally well tolerated in response to a 20 km cycling time trial and in a cycling focused population (Smith et al 2013), field-based studies report average ad libitum carbohydrate intakes during a marathon of 35 g·h -1 , and ultra-marathon events ranging from 24 to 37 g·h -1 , irrespective of ultra-marathon runners carrying multiple-transportable carbohydrate rich foods and fluids equating to >60 gCHO·h -1 in the latter (Costa et al 2013;Pfeiffer et al 2012). …”
Section: Introductionmentioning
confidence: 99%